G−0.02−0.07, the compact H ii region complex nearest to the galactic center with ALMA. (21st November 2019) - Tsuboi, Masato; Kitamura, Yoshimi; Uehara, Kenta; Miyazaki, Atsushi; Miyawaki, Ryosuke; Tsutsumi, Takahiro; Miyoshi, Makoto
Abstract: We have observed the compact H ii region complex nearest to the dynamical center of the Galaxy, G−0.02−0.07, using ALMA in the H42α recombination line, CS J = 2–1, H 13 CO + J = 1–0, and SiO v = 0, J = 2–1 emission lines, and the 86 GHz continuum emission. The H ii regions HII-A to HII-C in the cluster are clearly resolved into a shell-like feature with a bright half and a dark half in the recombination line and continuum emission. The analysis of the absorption features in the molecular emission lines show that H ii -A, B, and C are located on the near side of the "Galactic center 50 km s −1 molecular cloud" (50MC), but HII-D is located on the far side of it. The electron temperatures and densities ranges are T e = 5150–5920 K and n e = 950–2340 cm −3, respectively. The electron temperatures in the bright half are slightly lower than those in the dark half, while the electron densities in the bright half are slightly higher than those in the dark half. The H ii regions are embedded in the ambient molecular gas. There are some molecular gas components compressed by a C-type shock wave around the H ii regions. From the line width of the H42α recombination line, the expansion velocities of HII-A, HII-B, HII-C, and HII-D are estimated to be V exp = 16.7, 11.6, 11.1, and 12.1 km s −1, respectively. The expansion timescales of HII-A, HII-B, HII-C, and HII-D are estimated to be t age ≃ 1.4 × 10 4, 1.7 × 10 4, 2.0 × 10 4, and 0.7 × 10 4  yr, respectively. The spectral types of the central stars from HII-A to HII-D are estimated to be O8V, O9.5V, O9V, and B0V, respectively. These derived spectral types are roughly consistent with the previous radio estimation. The positional relation among the H ii regions, the SiO molecule enhancement area, and Class-I maser spots suggest that a shock wave caused by a cloud–cloud collision propagated along the line from HII-C to HII-A in the 50MC. The shock wave would have triggered the massive star formation.